2021
DOI: 10.1093/jamia/ocab220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the International Classification of Health Interventions (ICHI) in the coding of common surgical procedures

Abstract: Objective : To evaluate the International Classification of Health Interventions (ICHI) in the clinical and statistical use cases. Materials and Methods : We identified 300 most-performed surgical procedures as represented by their display names in an electronic health record. For comparison with existing coding systems, we coded the procedures in ICHI, SNOMED CT, International Classification of Diseases (ICD)-10-PCS, and CCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the class on surgery and invasive interventions, it was proposed to use ICHI for the coding of interventions. Some studies have shown that ICHI, in comparison to other intervention classification systems, has a better performance in registering the patient's information in the electronic health record 48 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the class on surgery and invasive interventions, it was proposed to use ICHI for the coding of interventions. Some studies have shown that ICHI, in comparison to other intervention classification systems, has a better performance in registering the patient's information in the electronic health record 48 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that ICHI, in comparison to other intervention classification systems, has a better performance in registering the patient's information in the electronic health record. 48 For a complete registry of the surgical intervention data, in addition to the surgical/invasive procedures class, a separate class had also been considered for registering the complication surgical procedure. In the international registry of vertebral column Spine Tango, 11 the postoperative complications data elements had been propounded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) has chosen to incorporate all health treatments in a new categorization known as the International Classification of Health Interventions (ICHI) (Paviot et al, 2011;Aljunid et al, 2015). ICHI covers diagnostics, medicine, surgery, mental health, primary care, medical aids, functional support, rehabilitation, traditional medicine, and public health (Fung et al, 2021).…”
Section: Ii133 International Classification Of Health Interventions (...mentioning
confidence: 99%
“…As suggested in the literature review, the World Health Organization family of international classifications (WHO) is an integrated set of classifications that serve as a global language for health information and consists of three reference classifications: the International Classification of Diseases (ICD), the International Classification of Functioning, Disability and Health (ICF), and the International Classification of Health Interventions (ICHI) (Fung et al, 2021). The use of ICD to classify illnesses has expanded dramatically in recent years (Harrison et al, 2021).…”
Section: Iv1 Introductionmentioning
confidence: 99%